Autologous cord blood mononuclear cell infusion for the prevention of bronchopulmonary dysplasia in very preterm monozygotic twins: A study protocol for a randomized, placebo-controlled, double-blinded multicenter trial - Zhuxiao, Ren; Ruoyu, Huang; Liling, Yang; Xuejun, Ren; Chunhui, Yang; Wanfen, Ruan; Zhifeng, Chen; Yiheng, Dai; Qi, Zhang; Wei, Wei; Zhipeng, Liu; Jingjun, Pei; et al. (Frontiers in Pediatrics, 2022)
Background: Preterm associated complications are still the main causes of neonatal death. The survivors are faced with short and long-term complications. Among all the complications, bronchopulmonary dysplasia (BPD) remains the first important cause of neonatal mortality and morbidity. Current existing treatments do not address this main preterm complication. Cord blood is regarded as a convenient source of stem cells. The paracrine factors of stem cells contribute to tissue repair and immune modulation. Our and others’ clinical studies have showed cord blood cells infusion are both safe and possibly effective in prevention and treatment for BPD. The therapeutic use of cord blood has emerged as a promising therapy. However, the genetic heterogeneity between control and intervention groups may decrease the comparability especially among small sample trials. The purpose of this study protocol is to investigate the effects of infusion of autologous cord blood mononuclear cells (ACBMNC) for the prevention of BPD in very preterm monozygotic twins less than 32 gestation weeks. Methods: In this prospective, randomized, placebo controlled, double-blinded multi-center clinical trial, 60 pairs of monozygotic twins preterm neonates less than 32 weeks admitted to Neonatal Intensive Care Unit (NICU) are randomly assigned to receive intravenous ACBMNC infusion (targeted at 5 ×107 cells/kg) or placebo (normal saline) within 24 hours after birth in a 1:1 ratio inside the twins. The primary outcome will be survival without BPD at 36 weeks of postmenstrual age. The secondary outcomes will include the mortality rate, BPD severity, other common preterm complication rates, respiratory support duration, length and cost of hospitalization, and long-term respiratory and neurodevelopmental outcomes during a 2-year follow-up. Further, we will perform single-cell RNA sequencing for cord blood cells, and the blood cells 3-10 days after intervention, and detect reactive oxygen species and inflammatory cytokines. Conclusion: This will be the first randomized, placebo controlled, double-blinded trial to evaluate the efficacy of ACBMNC infusion to prevent BPD in monozygotic twin premature infants and investigate the underlying protective mechanisms. The results of this trial will provide valuable clinical evidence for translational application of cord blood cells therapy in very preterm infants.